2009
DOI: 10.1002/em.20488
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2E1 and head and neck cancer: Interaction with genetic and environmental risk factors

Abstract: The present case-control study investigates the association of polymorphisms in cytochrome P450 2E1 (CYP2E1), involved in the metabolism of tobacco carcinogens and alcohol, with Head and Neck Squamous Cell Carcinoma (HNSCC). In addition, the interaction of CYP2E1 (CYP2E1*5B and CYP2E1*6) with other genetic factors (null genotype of glutathione-S-Transferase M1, GSTM1, X-Ray Repair Cross Complementing Group I, XRCC1 (Arg194Trp), and environmental risk factors such as alcohol and tobacco in modifying HNSCC risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
3
21
1
Order By: Relevance
“…Of these, two papers were excluded due to the fact that they did not evaluate the association between HNC risk and XRCC1 polymorphisms [23,24]. Subsequently, five studies were excluded because of the lack of useful genotype data [2529]. In the remaining 31 studies, two papers were excluded because of overlapping data [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, two papers were excluded due to the fact that they did not evaluate the association between HNC risk and XRCC1 polymorphisms [23,24]. Subsequently, five studies were excluded because of the lack of useful genotype data [2529]. In the remaining 31 studies, two papers were excluded because of overlapping data [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…One study [18] was discarded for insufficient data (although we tried to contact the authors to query the data), two [19,20] were discarded as being studies on leukoplakia. As shown in table 1, 21 case-control studies finally met our criteria for inclusion [2,3,7,21-38]. 21 studies were identified for the CYP2E1 -PstI/RsaI polymorphism, including a total of 4951 cases and 5995 controls, and for the DraI polymorphism 9 studies were identified covering a total of 2510 cases and 2162 controls.…”
Section: Resultsmentioning
confidence: 99%
“…It is hypothesized that part of the susceptibility to head and neck cancer may be determined by the inter-individual differences in the bioactivation of procarcinogens and detoxification of carcinogens. CYP2E1 , which is a major component of the microsomal system involved in the metabolism of ethanol and acetone among phase I enzymes, has been widely studied as a cause of susceptibility to head and neck cancer [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in genes encoding for metabolism of alcohol to acetaldehyde [alcohol dehydrogenase gene family (ADH)] and from acetaldehyde to acetate [aldehyde dehydrogenase 2 (ALDH2)], and CYP2E1 polymorphisms, are suspect in HNC and other alcohol-related cancer aetiology [10][11][12][13][14][15][16][17][18][19]. In particular, a significant protective effect of two single nucleotide polymorphisms (SNPs) towards upper aero-digestive tract cancer (UADT) was reported for two alcohol dehydrogenase genes: ADH1B (rs1229984) and ADH7 (rs1573496) [20].…”
Section: Introductionmentioning
confidence: 99%